Ain Ni Ain Philosophy in Peace Counseling : A Cultural Approach to Conflict Resolution between That Kei Communities in Sorong City - Abdul Latif Raharusun; Alif Hasanah; Rosdiana Rosdiana (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2026)
Local wisdom plays a strategic role in maintaining social cohesion and resolving conflicts in multicultural societies. Ain Ni Ain is a cultural value upheld by the Kei ethnic community of Southeast Maluku, Indonesia. This philosophy, which literally means “one belongs to another,” emphasizes brotherhood, solidarity, and collective responsibility as the foundation of social relations. However, these values have experienced cultural shifts in the urban context of Sorong City, Southwest Papua. This study aims to analyze the implementation of Ain Ni Ain values within a peace counseling approach as a strategy for conflict resolution among the Kei community in Sorong City. The study employed a qualitative case study design. Data were collected through in-depth interviews with customary leaders, religious leaders, counselors, and members of the Kei community involved in or affected by conflicts, supported by participatory observation. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation of sources and techniques. The findings indicate that Ain Ni Ain remains relevant in peace counseling practices through community deliberation, customary mediation, reinforcement of collective moral commitments, and spiritual legitimization by traditional and religious leaders, with counselors acting as facilitators of reflective dialogue in reconciliation processes. These findings suggest that integrating local cultural values into counseling practices can strengthen community-based conflict resolution and contribute to the development of culturally grounded peace counseling in multicultural societies.